THE INFLUENCE OF SELF-ESTEEM ON PSYCHOLOGICAL-WELL-BEING THROUGH STRATEGY-COPING MEDIATION IN GRADE XII STUDENTS OF MEDAN STATE HIGH SCHOOL - Surbakti, Amanah; Parinduri, Rusdah; Delyani, Rifatun Nihaya Rambe; Pulungan, Fatmawina; Nainggolan, Rani; Situmorang, Renatalina (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
When students are in class XII, students experience stress in determining their future. There are also students who are under pressure from their parents' wishes in determining their college major. This research aims to manage stress experienced by students through Strategy-Coping, and to see the influence of Self-Esteem on Psychological-Well-Being through Strategy-Coping. The research used quantitative methods by distributing questionnaires to 200 class XII students at SMA Negeri Medan. The scales used are: 1) Adolecents-COPE (Patterson & McCubbin) 2) Psychological-Well-Being (Ryff) 3) Self-Esteem (Rosenberg). Data analysis using SPSS 26 for Windows software. The calculated r value in a 2-sided test with a Siq. of 0.05 and a number of respondents of 200 is 0.1388. The validity test results stated that 55 items had a calculated r_value > 0.1388, all items were declared valid. All instruments were declared reliable because the results of the Statistical Reliability test showed a Cronbach Alpha value of <0.888 or a value of >0.6. Heeroscedasticity test results show that heteroscedasticity does not occur because the Siq values for all variables are > 0.05. The results of the hypothesis test show that Strategy-Coping mediates the relationship between Self-Esteem and Psychological-Well-Being, so that the influence of Self-Esteem on Psychological-Well-Being becomes stronger after being mediated by Strategy-Coping. The results of research on class XII students of Medan State High School showed high Self-Esteem and Psychological-Well-Being in students. High Self-Esteem is the way a person views, appreciates and loves themselves well and can influence high Psychological Well-Being (PWB) so that a person has a positive, balanced and sustainable life and has a positive attitude towards themselves and other people, so they can manage and control stress through Strategy-Coping. The results of students' Problem-focused-coping were higher than Emotional-focused-coping.